2020
DOI: 10.1097/brs.0000000000003557
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Cage Subsidence in Patients Received Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Study Design. A retrospective cohort study. Objective. To determine the risk factors of cage subsidence in patients undergoing minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) and its correlation with patient-reported outcomes. Summary of Background Data. Cage subsidence is among the cage-related complications after TLIF and may lead to poor outcomes. Few studies have addressed the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 28 publications
3
67
1
2
Order By: Relevance
“…Postoperative intervertebral height was found to remain significantly higher in OLIF until the final evaluation. Endplate subsidence has been reported to be 30–70% for TLIF 14 18 and 11–30% for OLIF 19 22 , According to a biomechanical study by Lu et al 10 , as the surface area of the OLIF cage is much larger than that of the TLIF cage, the stresses on the vertebral endplates and cancellous bone are distributed and less susceptible to subsidence. Lin et al 4 also reported a higher cage subsidence rate in minimally invasive (MI) TLIF than in OLIF because the OLIF cage is placed at the strongest point on both ends of the vertebral endplate, whereas the TLIF cage is mostly placed near the center of the vertebral endplate.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative intervertebral height was found to remain significantly higher in OLIF until the final evaluation. Endplate subsidence has been reported to be 30–70% for TLIF 14 18 and 11–30% for OLIF 19 22 , According to a biomechanical study by Lu et al 10 , as the surface area of the OLIF cage is much larger than that of the TLIF cage, the stresses on the vertebral endplates and cancellous bone are distributed and less susceptible to subsidence. Lin et al 4 also reported a higher cage subsidence rate in minimally invasive (MI) TLIF than in OLIF because the OLIF cage is placed at the strongest point on both ends of the vertebral endplate, whereas the TLIF cage is mostly placed near the center of the vertebral endplate.…”
Section: Discussionmentioning
confidence: 99%
“…Cage subsidence (CS) is one of the complications that results in gradual loss of disc height (DH) and segmental lordosis (SL). Previous studies have suggested that CS is associated with osteoporosis, excessive distraction of the intervertebral space, and damage to the endplate [7][8][9][10]. Modic changes (MCs) in the lumbar endplate and subendplate bones on magnetic resonance imaging (MRI) images are classified into three types: MCs-1 is considered as the inflammatory phase or edema phase; MCs-2 is considered as the fatty phase or yellow marrow phase; MCs-3 is considered as the osteosclerosis phase.…”
Section: Introductionmentioning
confidence: 99%
“…Modern intervertebral fusion is mostly achieved by implanting an intervertebral fusion Cage (Cage). As a permanent implant in the human body, Cage plays an important role in promoting intervertebral bony fusion and maintaining early biomechanical stability [22]. At rst, clinicians used two Cages to implant the intervertebral space [23].…”
Section: Discussionmentioning
confidence: 99%